Electroacupuncture Reduces Aβ Production and BACE1 Expression in SAMP8 Mice - Dong, Wei-Guo; Wang, Feng; Chen, Ye; Zheng, Xue-Hua; Xie, Yong-Cai; Guo, Wan-Qing; Shi, Hong (Frontiers in Aging Neuroscience, 2015)
Electroacupuncture (EA) has been reported to have beneficial effects on Alzheimer's disease (AD). BACE1 (β-site amyloid precursor protein-cleaving enzyme 1) is involved in the abnormal production of amyloid-β plaque (Aβ), a hallmark of AD pathophysiology. Thus, the present study investigated the effects of EA on memory impairment, Aβ production, and BACE1 expression in SAMP8 mice. We found that EA improved spatial learning and memory impairment of SAMP8 mice. Furthermore, EA attenuated Aβ production and repressed the expression of BACE1 in the hippocampus of SAMP8 mice. Taken together, our results suggest that EA could have a potential therapeutic application in AD and that BACE1 may be an important target of EA in the treatment of AD.